Association Between Insulin Resistance, Glucose Intolerance, and Hypertension in Pregnancy - Negrato, Carlos Antonio [UNESP]; Jovanovic, Lois; Tambascia, Marcos Antonio; Geloneze, Bruno; Dias, Adriano [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (Mary Ann Liebert, Inc., 2009)
There is an association between insulin resistance, glucose intolerance, and essential hypertension, but the relation between insulin resistance, glucose intolerance, and hypertension diagnosed during pregnancy is not well understood. Transient hypertension of pregnancy, the new-onset nonproteinuric hypertension of late pregnancy, is associated with a high risk of later essential hypertension and glucose intolerance; thus, these conditions may have a similar pathophysiology. To assess the association between insulin resistance, glucose intolerance, essential hypertension, and subsequent development of proteinuric and nonproteinuric hypertension in pregnancy in women without underlying essential hypertension, we performed a prospective study comparing glucose (fasting, I and 2 hours postglucose load), insulin, glycosylated hemoglobin (HbA1c), high-density lipoprotein cholesterol (HDL-C), and triglycerides levels on routine screening for gestational diabetes mellitus. Women who developed hypertension in pregnancy (n = 37) had higher glycemic levels (fasting, 1 and 2 hours postglucose load) on a 100-gram oral glucose loading test, although only the fasting values showed a statistical significance (p < 0.05), and a significantly higher frequency of abnormal glucose loading tests, two hours after glucose load (>= 140 mg/dL) (p < 0.05) than women who remained normotensive (n = 180). Glucose intolerance was common in women who developed both subtypes of hypertension, particularly preeclampsia. Women who developed hypertension had greater prepregnancy body mass index (p < 0.0001), higher frequency and intensity of acanthosis nigricans (p < 0.0001), and higher baseline systolic and diastolic blood pressures (p <= 0.0001 for both), although all subjects were normotensive at baseline by study design; they also presented lower levels of HDL-C (p < 0.05). However, after adjustment for these and other potential confounders, an abnormal glucose loading test remained a significant predictor of development of hypertension (p < 0.05) and, specifically, preeclampsia (p < 0.01). There was a trend toward higher insulin and homeostasis model assessment-insulin resistance (HOMA-IR) levels in women developing any type of hypertension. When comparing women that remained normotensive to term with those with transient hypertension and preeclampsia, the preeclamptic women were born with lower weight (p < 0.05) and shorter length (p < 0.005); at screening they were older (p < 0.005), showed higher frequency and intensity of acanthosis nigricans (p < 0.0001), had higher prepregnancy BMI (p < 0.0005), as well as higher baseline systolic and diastolic blood pressures (p <= 0.0001 for both). They also showed higher HOMA-IR levels that did not show a statistical significance. When glucose tolerance status was taken in account, an association was found between increasing indexes of hypertension (p < 0.05) and of HOMA-IR (p < 0.05) with the worsening of glucose tolerance. These results suggest that insulin resistance and relative glucose intolerance are associated with an increased risk of new-onset hypertension in pregnancy, particularly preeclampsia, and support the hypothesis that insulin resistance may play a role in the pathogenesis of this disorder.